Teacher Communication Style in Achieving Learning Success in the Classroom - Afida Novitasari; Vicky Fauziah; Irmayanti Irmayanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to determine the teacher's communication style and how this style contributes to the achievement of successful learning at SDN Sempu 1, Serang City. In this study, researchers used a type of qualitative research with descriptive methods and data collection techniques by interviews and observations. The results showed that the teacher's communication style greatly influenced the motivation of students and the achievement of successful learning in the classroom. The teacher's communication style is not only important in dealing with students, but also in communicating with parents of students to support learning at home. Teachers who are able to communicate well and adjust the style of communication with students are able to create a fun and productive learning environment, which can improve academic achievement and emotional well-being of students. Therefore, education must equip teachers with better communication skills to ensure successful learning in the classroom. In conclusion, the results of this study confirm that the teacher's communication style is an important factor in achieving successful learning in the classroom. Teachers must pay close attention to the use of communication styles with students and parents to build a positive and effective learning environment. This research is expected to provide input and reference for decision makers in the field of education, particularly in improving teacher communication skills to help achieve better learning goals.